Multiview Image Acquisition and Projection - Son, Jung-Young; Saveljev, Vladimir V.; Kim, Jai-Soon; Kwack, Kae-Dal; Kim, Sung-Kyu (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
A solution for describing both the multiview image set, obtained with a parallel camera layout, and the perceived image in a projection-type full parallax multiview imaging system with a parallel projector layout, is derived. This is done with the use of 4x4 homogenous matrices to quantitatively analyze the image quality in the system. The solution provides a means of finding properties and/or behavior of the perceived image changes depending on the viewer's position in the system. The solution can analytically describe the appearance of three-dimensional images in the space generated by the multiview image set displayed on a projection screen.